Review Article on the Most Common Bacteria in Hospital Pollution - Gharbi, Abbas Noori; Rasheed, Muhammad Sabah; mdhat, Mohamed widad; ahmed, Amenah mahmood (American Journal of Biology and Natural Sciences, 2024)
The pollution of indoor hospital environments has become increasingly concerning since pollutants produced due to inadequate waste management and inappropriate chemical disposal have shown considerable negative influence on both the hospital staff and patients. Generally, large amounts of polyethylene, rubber, wood, cardboard, paper, cotton wool, food, carbon-based objects, ink-paper, X-ray solutions, and machine oil are extensively used in hospitals, and once these products become outdated, they are generally thrown away to landfills without considering the potential of soil and environmental pollution. Besides chemical wastes, other remarkable indoor hospital pollutants such as chemicals and biological materials, including tissue, bone, and biohazard materials from human infections and hospital surgeries, could potentially spread higher concentrations of several more diverse bacterial hazards than similar outdoor environmental conditions. Hospital staff and day admissions are mostly at risk from surfaces that are highly exposed to various pollution materials, such as those on operation theater floors and table surfaces, and many departments, including the surgical department. Microbial pollution may lead to severe infections in humans, causing injuries from cutting instruments during surgery and affecting wound tissues.